Effect of wall corrugation on local convective heat transfer in coiled tubes. (October 2016) - Bozzoli, Fabio; Cattani, Luca; Rainieri, Sara
Highlights: The local convective heat transfer coefficient in a corrugated coil was estimated. The procedure was based on the solution of the Inverse Heat Conduction Problem. The solution strategy was based on the filtering technique. The results highlighted the effect of both wall curvature and of wall corrugation. The results are useful in the design of innovative coiled tube heat exchangers. Abstract: The present paper presents the application of an inverse analysis approach to experimental infrared temperature data with the aim of estimating the local convective heat transfer coefficient for forced convection flow in coiled pipe having corrugated wall. The estimation procedure here adopted is based on the solution of the Inverse Heat Conduction Problem within the wall domain, by adopting the temperature distribution on the external coil wall as input data of the inverse problem: the unwanted noise is filtered out from the infrared temperature maps in order to make feasible the direct calculation of its Laplacian, embedded in the formulation of the Inverse Heat Conduction Problem, in which the convective heat transfer coefficient is regarded to be unknown. The results highlighted the local effects of both wall curvature and of wall corrugation on the convection heat transfer augmentation mechanism.